MetricSplit: an automated notation of rhythm aligned with metric structure. Issue 1 (2nd January 2019) - Lepper, Markus; Trancón y Widemann, Baltasar
Abstract : For any musical rhythm given by a sequence of duration values as rational numbers, traditional common western notation (CWN) provides infinite possibilities for its notation, using the standard devices: note symbols, prolongation dots, ties, and proportional brackets. But given additionally a musical meter, which in CWN is some hierarchical organization of time points, repeated with every measure, this number is significantly reduced to those aligned with both meter and rhythm. For an automatically generated rhythm, for instance by algorithmic composition or analysis, such a notation should be found automatically, too. This is achieved by the algorithmmetric Split, presented in this paper. The necessary analysis and modelling shall also serve as a contribution to theoretical discussion.